LA ECONOMÍA DE TOMÁS DE MERCADO. UN ANÁLISIS A TRAVÉS DE SUMMA DE TRATOS Y CONTRATOS - Gallego Morales, Daniel José (REVISTA PROCESOS DE MERCADO, 2022)
Spanish Scholastics were somewhat forgotten until José Larraz and Marjorie Grice-Hutchinson, in the middle of the last century, observed in their studies of scholastic authors that they had special intellectual concerns about the economic aspects that surrounded them. Although it is true that they did not analyse them directly, but with the perspective provided by theology, they found certain concepts and realities that are of utmost importance for economics in general, and in particular the Austrian School. Moreover, the discovery had a major impact on cultural, social and, especially, economic aspects. Theeconomy and markets underwent an unprecedented revolution in which a moral reference was needed to guide the behaviour of individuals. It is in this context that the work of Tomás de Mercado, Summa de tratos y contratos, waswritten. The author was concerned about the legitimacy and lawfulness of contracts and exchanges, that were growing exponentially. He therefore wrote a moral guide to determine what should be the right and lawful behaviour of individuals, through a deep knowledge of their economic and social environment.